2004
DOI: 10.1080/02841850410006876
|View full text |Cite
|
Sign up to set email alerts
|

Volume rendering compared with maximum intensity projection for magnetic resonance angiography measurements of the abdominal aorta

Abstract: VRT is not suitable for diameter measurements of the abdominal aorta with fixed parameter settings but may be useful with user-selected settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Because single‐voxel thick reformations show only short vascular segments, maximum intensity projection (MIP) is a useful complementary postprocessing technique for combining information from multiple slices to see longer segments of vessels (99–103). Using MIP, the user specifies the subvolume thickness and obliquity.…”
Section: Postprocessing and Displaymentioning
confidence: 99%
“…Because single‐voxel thick reformations show only short vascular segments, maximum intensity projection (MIP) is a useful complementary postprocessing technique for combining information from multiple slices to see longer segments of vessels (99–103). Using MIP, the user specifies the subvolume thickness and obliquity.…”
Section: Postprocessing and Displaymentioning
confidence: 99%
“…While existing methods are limited to applying vessel enhancement filters to either the original non-projected 3D images or a single MIP through the entire imaged volume (Gao et al, 2011;Hsu et al, 2017;Phellan and Forkert, 2017), there has been little investigation of the influence of projection thickness on the effectiveness of vessel segmentation. Of the few studies reported, one showed similarity between vessel radii measurements extracted from parameter-dependent MIP MRA and digital subtraction angiography derived from high contrast x-ray images (Persson et al, 2004). Another group showed that MIP images using a slab thickness of 8 mm are superior in the detection of pulmonary nodules (Kawel et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In a material of 20 patients previously examined with gadolinium-enhanced MRA and with DSA for abdominal aortic aneurysm, rendering of MRA 3D datasets was performed with three new techniques for standardized TF. Details of the MRA sequences and DSA procedure have been described previously (3,10). For the present study, all MRA datasets were transferred to a 3D workstation (Leonardo with 3D MIP software and Inspace interactive 3D Viewer; Siemens Medical Solutions Computed Tomography, Forchheim, Germany) equipped with a real-time volume-rendering graphic accelerator card (VolumePro 1000; TeraRecon, Inc., San Mateo, Calif., USA).…”
Section: Methodsmentioning
confidence: 99%